1969
DOI: 10.1002/ijc.2910040609
|View full text |Cite
|
Sign up to set email alerts
|

Malignant and transforming activity of rous sarcoma virus. II. The study of variants of rous sarcoma virus isolated from mouse tumours

Abstract: Virus variants from Af mouse tumours induced by syngeneic cultured cells infected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1969
1969
1986
1986

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Furthermore, the duck-adapted virus had altered surface antigenic properties. A similar phenomenon has also been noted with RSV that has been rescued from transformed rat cells (5)(6)(7)(8)(9)(10)(11)(12). These findings led Altaner and Temin (6) to suggest that the alteration of physical and biological properties in the virus may reflect recombination between viral and host genetic material.…”
supporting
confidence: 71%
“…Furthermore, the duck-adapted virus had altered surface antigenic properties. A similar phenomenon has also been noted with RSV that has been rescued from transformed rat cells (5)(6)(7)(8)(9)(10)(11)(12). These findings led Altaner and Temin (6) to suggest that the alteration of physical and biological properties in the virus may reflect recombination between viral and host genetic material.…”
supporting
confidence: 71%
“…This rat 'variant' of B77 was shown to be antigenically modified and had increased transforming activity on rat cells [Altaner and Temin, 1970] and hamster cells [Svec et al, 1970]. Kryukova et al [1968Kryukova et al [ ,1970, Obukh and Kryukova [1969], and found that tumors are efficiently produced in adult mice if fibroblasts are first infected in vitro with CZ-RSV and then transferred to syngeneic animals. From such tumors 'var iants' again were obtained which showed high oncogenicity for mice and hamsters.…”
Section: The Src Gene Product and Cell Transformationmentioning
confidence: 99%